G477 Identification of novel par2 mutation in thrombotic microangiopathy. (27th April 2015) - Walsh, P; Asfahani, R; Osman, G; Hothi, D; Waters, A
Abstract : Atypical Haemolytic Uraemic Syndrome (aHUS) is a rare cause of renal failure, occurring as a result of glomerular endothelial cell injury, with a prevalence of 3–5 per million. The clinical features consist of recurrent episodes of haemolytic anaemia, thrombocytopaenia and renal failure with biopsy evidence of thrombotic microangiopathy. Mutations in complement regulatory genes account for approximately 70% of cases. More recently, components of the coagulation cascade, such as DGKE, have been implicated in the aetiopathogenesis of aHUS. We have identified a novel mutation in protease–activated receptor 2 (PAR2) in a patient with an aHUS phenotype. Methods: Whole Exome Sequencing (WES) was performed on a child presenting at the age of 3 years with nephrotic range proteinuria and biopsy evidence of thrombotic microangiopathy, thrombocytopaenia and haemolytic anaemia. One year from presentation, his renal function recovered to baseline but he continues to experience episodic haemolytic anaemia and thrombocytopaenia. Of note, there is a familial history of relapsing thrombocytopaenia affecting the patient's father and aunt. Results: WES did not demonstrate any mutations in known aHUS genes. A novel mutations in PAR2 (Y345H) was identified, in silico analysis of this classified this as deleterious. This mutation was not detected in databases of healthy controls. Sequence analysis demonstrated segregation in affected family members (Figure 1 ) Western blot analysis suggests reduced PAR2 expression in the patient's serum compared to controls. We also show that PAR2 is expressed in glomerular cells (Figures 2 and 3 ) Discussion: PAR2 is a G-protein coupled receptor, which is activated by a number of pro-inflammatory and coagulation mediators. Activation of this receptor causes a positive feedback loop, leading to a pro-thrombotic state that may result in pathological platelet activation and endothelial dysfunction. As there are high levels of PAR2 in the kidney, this pro-thrombotic state may lead to the thrombotic microangiopathy seen in aHUS. PAR2 has additional roles in complement regulation that are less well defined. It is known to cause down–regulation of DAF, which is an important regulator of the complement pathway. Further analysis of genetically undefined cases of TMA and MPGN are required for PAR2 mutational screening to determine whether PAR2 represents a unique pathway in these rare renal phenotypes.